Preparation method and application of composite ferrite loaded magnetic calcium sulfate whisker

By preparing magnetic calcium sulfate whiskers loaded with composite ferrite, the problem of removing heavy metal ions in electroplating wastewater is solved, and the ability to efficiently remove carbonyl sulfur in gas purification is shown, achieving environmentally friendly and economical treatment effects.

CN119869437AActive Publication Date: 2025-04-25JIANGSU CHANGHUAN ENVIRONMENTAL TECH CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510234940.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-28
Publication Date
2025-04-25
Estimated Expiration
2045-02-28

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove heavy metal ions when treating electroplating wastewater, and may produce toxic waste or cause new pollution.

Method used

The preparation method of magnetic calcium sulfate whiskers supported by composite ferrite is adopted to convert heavy metal ions in electroplating wastewater into solid chemicals and use its catalytic activity to remove carbonyl sulfur in the gas.

Benefits of technology

The effective removal of heavy metal ions in electroplating wastewater is achieved, the generation of toxic waste is avoided, and the ability to efficiently remove carbonyl sulfur in gas purification is shown.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119869437A_ABST
    Figure CN119869437A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of composite ferrite-loaded magnetic calcium sulfate whiskers, and the preparation method comprises the following steps: pretreating electroplating wastewater with ferrous sulfate, then adding ferroferric oxide nanoparticles, mixing and stirring, adding calcium oxide, aging, and then carrying out solid-liquid separation and drying to obtain the composite ferrite-loaded magnetic calcium sulfate whiskers. The magnetic calcium sulfate whisker loaded with the composite ferrite nanoparticles is obtained; in addition to Cr < 6 + > and Cr < 3 + >, the electroplating wastewater also contains at least one of Ni < 2 + >, Cu < 2 + >, Mn < 2 + >, Fe < 2 + > and Fe < 3 + >. According to the method, heavy metal ions in the electroplating wastewater can be directly converted into reusable and practical solid chemicals, meanwhile, no toxic waste is generated, no new pollution is caused, and carbonyl sulfide in gas can be effectively removed through the obtained solid chemicals.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method and application of composite ferrite-loaded magnetic calcium sulfate whiskers, belonging to the technical field of heavy metal recovery. Background Art

[0002] Electroplating wastewater refers to all wastewater generated by the electroplating workshop during the electroplating production process. According to the different functions and properties required by the electroplating products, the production processes are different, which leads to complex types of wastewater and water quality, and the composition is difficult to control. Wastewater often contains heavy metal ions such as chromium, cadmium, nickel, copper, and lead. Therefore, in order to facilitate the subsequent treatment of wastewater, it is usually diverted and treated separately. Electroplating wastewater is further divided into electroplating wastewater containing mainly heavy metals, such as nickel-containing wastewater, copper-containing wastewater, chromium-containing wastewater, and chromium-containing wastewater. The treatment and disposal of electroplating wastewater has become an urgent problem that the industry needs to solve.

[0003] Heavy metal recovery is an important part of sustainable development and environmental protection goals. Various recovery technologies have been developed, including adsorption, precipitation, ion exchange, solvent extraction, membrane separation, electrochemical methods, microbial methods, etc. These methods can recover heavy metals from wastewater very well, but previous studies have also shown that most methods still have disadvantages, such as the generation of complex and diverse metal sludge, residual toxic waste or the creation of new pollution. Summary of the invention

[0004] The purpose of the present invention is to provide a preparation method and application of composite ferrite-loaded magnetic calcium sulfate whiskers, which can directly convert heavy metal ions in electroplating wastewater into solid chemicals without generating toxic wastes or causing new pollution. The obtained solid chemicals can also effectively remove carbonyl sulfide in the gas.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is:

[0006] A method for preparing composite ferrite-loaded magnetic calcium sulfate whiskers comprises pre-treating electroplating wastewater with ferrous sulfate, adding ferroferric oxide nanoparticles, mixing and stirring, adding calcium oxide, aging, solid-liquid separation, and drying to obtain magnetic calcium sulfate whiskers loaded with composite ferrite nanoparticles;

[0007] Among them, electroplating wastewater contains Cr 6+ Cr 3+ In addition, it also contains Ni 2+ , Cu 2+ , Mn 2+ , Fe 2+ , Fe 3+ At least one of .

[0008] Preferably, the electroplating wastewater contains Cr 6+ Cr 3+ 、Ni 2+ , Cu 2+ , Mn 2+ , Fe 2+ and Fe 3+ ;

[0009] Among them, Fe 2+ , Fe 3+ 、Ni 2+ , Cu 2+ , Mn 2+ Cr 3+ Cr 6+ The concentrations are 200-2000mg / L, 500-4000mg / L, 300-3000mg / L, 10-5000mg / L, 5-1000mg / L, 100-10000mg / L, and 400-8000mg / L respectively.

[0010] Preferably, the specific method of pretreatment is: adding ferrous sulfate heptahydrate into the electroplating wastewater and stirring for 40-80 minutes;

[0011] Among them, ferrous sulfate heptahydrate and Cr in electroplating wastewater 6+ The molar ratio is (5-30):1.

[0012] Preferably, the amount of ferrosoferric oxide nanoparticles added is 2-6 times the metal content in the electroplating wastewater.

[0013] Preferably, the particle size of the ferrosoferric oxide nanoparticles is 20 nm-1 mm.

[0014] Preferably, the pH of the solution after calcium oxide is added is 7-12.

[0015] Preferably, the aging conditions are: room temperature, 0.5-5h.

[0016] Preferably, the drying conditions are: 60-100°C, 3-10h.

[0017] The application of the composite ferrite-loaded magnetic calcium sulfate whiskers prepared by any of the above methods in gas purification is to remove carbonyl sulfide contained in the gas.

[0018] The beneficial effects of the present invention are:

[0019] Crystal seed assisted crystallization is a kind of "heteroepitaxy". Heterogeneous surfaces can act as crystal nuclei and provide active sites, so nucleation becomes energetically favorable, which changes the crystallization behavior and accelerates the crystallization process. Adding crystal seeds during the crystal synthesis process can increase the crystallization rate and inhibit the formation of unwanted phases, that is, produce a product selectivity effect, and cause local supersaturation of low-concentration solutions through their adsorption or other effects, thereby leading to induced crystallization. The present invention provides a load carrier for composite ferrite nanoparticles by forming calcium sulfate whiskers through crystal seed induced crystallization, and at the same time enables the composite ferrite nanoparticles to disperse the load, reducing the agglomeration between the composite ferrite nanoparticles, and laying a foundation for the subsequent improvement of the removal effect of carbonyl sulfide.

[0020] The magnetic calcium sulfate whiskers loaded with composite ferrites have catalytic activity and can convert carbonyl sulfide into easily handled products through oxidation or hydrolysis. The high specific surface area of ​​calcium sulfate whiskers has abundant adsorption sites, which enhances the enrichment of carbonyl sulfide and the efficiency of catalytic reaction. After the ferrite and calcium sulfate whiskers are combined, the chemical stability is enhanced and it can withstand complex environments. The magnetic properties of the material enable it to be quickly separated and recovered through an external magnetic field after the reaction, avoiding the high cost of traditional adsorbent filtration or centrifugation, and is suitable for continuous processing.

[0021] At the same time, the method is simple to operate, environmentally friendly, has low energy consumption and raw material costs, good economic benefits, is conducive to industrial-scale production, and has good prospects for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a SEM image of the magnetic calcium sulfate whisker precipitate of the composite ferrite nanoparticles obtained in Example 1.

[0023] Figure 2 This is the XRD pattern of the magnetic calcium sulfate whisker precipitate of the composite ferrite nanoparticles obtained in Example 1. DETAILED DESCRIPTION

[0024] Example 1

[0025] 4.46g of ferrous sulfate heptahydrate was added to 100ml of electroplating wastewater (containing 1000mg / L Cr 6+ , 1000mg / L Fe 2 + 、2000mg / L Fe 3+ 、1500mg / L Ni 2+ 、800mg / L Cu 2+ and 3000mg / L Cr 3+) was stirred for 60 minutes, and then 3 g of ferroferric oxide seed with a particle size of 20 nm was added. CaO was added under stirring to adjust the pH to 10, and then aged at room temperature for 2 hours. A solid precipitate and a supernatant were obtained by centrifugation. The solid precipitate was dried at 80°C for 6 hours and then ground to obtain a magnetic calcium sulfate whisker precipitate with composite ferrite nanoparticles loaded on the surface. Its SEM and XRD patterns are shown as follows: Figure 1 , 2 shown.

[0026] Depend on Figure 1 The left area shows that the calcium sulfate whiskers have a fibrous structure with uniform diameter and ferrite nanoparticles attached to the surface. The right area shows that the ferrite particles attached to the calcium sulfate whiskers are relatively uniform in size and regular in shape, almost spherical; the particle surface is relatively smooth, and only slight agglomeration exists between some particles.

[0027] Depend on Figure 2 The characteristic diffraction peaks of calcium sulfate and ferrite can be clearly observed. The diffraction peaks of the two phases are independent of each other, indicating that calcium sulfate and ferrite coexist in the product. The diffraction peaks of calcium sulfate mainly correspond to the typical crystal planes (020), (021) and (041) in its crystal structure. These peak positions indicate the presence of well-crystallized calcium sulfate phases in the sample. At the same time, the characteristic diffraction peaks of ferrite are also clearly visible, and their peak positions correspond to the crystal planes (311), (220) and (400) of the spinel structure. The peak shape is sharp, indicating that the ferrite nanoparticles have good crystallinity.

[0028] The removal rates of Cr, Fe, Ni and Cu in electroplating wastewater are 99.2%, 99.9%, 99.9% and 99.5% respectively. Magnetic calcium sulfate whiskers loaded with composite ferrite nanoparticles on the surface are used to treat toxic gas carbonyl sulfide, with a carbonyl sulfide concentration of 500ppm, nitrogen as the balance gas, and a reaction space velocity of 15000h -1 The reaction temperature is 150°C, the water vapor content is 10%, and the loading amount in the hydrolysis tower is 3% of the tower height. Under the above conditions, after 300 minutes, the removal efficiency of carbonyl sulfide is 93%.

[0029] Example 2

[0030] 4.46g of ferrous sulfate heptahydrate was added to 100ml of electroplating wastewater (containing 1000mg / L Cr 6+ , 1000mg / L Fe 2 + 、2000mg / L Fe 3+ 、1500mg / L Ni 2+ 、800mg / L Cu 2+ and 3000mg / L Cr 3+), stirred for 60 minutes, then added 3g of ferroferric oxide seed with a particle size of 20nm, added CaO under stirring to adjust the pH to 7, and then aged at room temperature for 2h. Centrifuged to obtain a solid precipitate and a supernatant, the solid precipitate was dried at 80℃ for 6h and then ground to obtain magnetic calcium sulfate whiskers with composite ferrite nanoparticles loaded on the surface.

[0031] The removal rates of Cr, Fe, Ni and Cu in electroplating wastewater are 98.1%, 99.7%, 80.2% and 93.8% respectively. Magnetic calcium sulfate whiskers loaded with composite ferrite nanoparticles on the surface are used to treat toxic gas carbonyl sulfide, with a carbonyl sulfide concentration of 500 ppm, nitrogen as the balance gas, and a reaction space velocity of 15000 h -1 The reaction temperature is 150°C, the water vapor content is 10%, and the loading amount in the hydrolysis tower is 3% of the tower height. Under the above conditions, after 300 minutes, the removal efficiency of carbonyl sulfide is 86%.

[0032] Example 3

[0033] 4.46g of ferrous sulfate heptahydrate was added to 100ml of electroplating wastewater (containing 1000mg / L Cr 6+ , 1000mg / L Fe 2 + 、2000mg / L Fe 3+ 、1500mg / L Ni 2+ 、800mg / L Cu 2+ and 3000mg / L Cr 3+ ), stirred for 60 minutes, then added 3g of ferroferric oxide seed with a particle size of 20nm, added CaO under stirring to adjust the pH to 8, and then aged at room temperature for 2h. Centrifuged to obtain a solid precipitate and a supernatant, the solid precipitate was dried at 80℃ for 6h and then ground to obtain magnetic calcium sulfate whiskers with composite ferrite nanoparticles loaded on the surface.

[0034] The removal rates of Cr, Fe, Ni and Cu in electroplating wastewater are 98.5%, 99.6%, 99.3% and 96.5% respectively. Magnetic calcium sulfate whiskers loaded with composite ferrite nanoparticles on the surface are used to treat toxic gas carbonyl sulfide, with a carbonyl sulfide concentration of 500 ppm, nitrogen as the balance gas, and a reaction space velocity of 15000 h -1 The reaction temperature is 150°C, the water vapor content is 10%, and the loading amount in the hydrolysis tower is 3% of the tower height. Under the above conditions, after 300 minutes, the removal efficiency of carbonyl sulfide is 88%.

[0035] Example 4

[0036] 4.46g of ferrous sulfate heptahydrate was added to 100ml of electroplating wastewater (containing 1000mg / L Cr 6+ , 1000mg / L Fe 2 + 、2000mg / L Fe 3+ 、1500mg / L Ni 2+ 、800mg / L Cu 2+ and 3000mg / L Cr 3+ ), stirred for 60 minutes, then added 3g of ferroferric oxide seed with a particle size of 20nm, added CaO under stirring to adjust the pH to 9, and then aged at room temperature for 2h. Centrifuged to obtain a solid precipitate and a supernatant, the solid precipitate was dried at 80℃ for 6h and then ground to obtain magnetic calcium sulfate whiskers with composite ferrite nanoparticles loaded on the surface.

[0037] The removal rates of Cr, Fe, Ni and Cu in electroplating wastewater are 99.1%, 99.5%, 99.3% and 97.8% respectively. Magnetic calcium sulfate whiskers loaded with composite ferrite nanoparticles on the surface are used to treat toxic gas carbonyl sulfide, with a carbonyl sulfide concentration of 500ppm, nitrogen as the balance gas, and a reaction space velocity of 15000h -1 The reaction temperature is 150°C, the water vapor content is 10%, and the loading amount in the hydrolysis tower is 3% of the tower height. Under the above conditions, after 300 minutes, the removal efficiency of carbonyl sulfide is 91%.

[0038] Example 5

[0039] 4.46g of ferrous sulfate heptahydrate was added to 100ml of electroplating wastewater (containing 1000mg / L Cr 6+ , 1000mg / L Fe 2 + 、2000mg / L Fe 3+ 、1500mg / L Ni 2+ 、800mg / L Cu 2+ and 3000mg / L Cr 3+ ), stirred for 60 minutes, added 3g of ferroferric oxide seed with a particle size of 20nm, added CaO under stirring to adjust the pH to 11, and then aged at room temperature for 2h. Centrifuged to obtain a solid precipitate and a supernatant, the solid precipitate was dried at 80℃ for 6h and then ground to obtain magnetic calcium sulfate whiskers with composite ferrite nanoparticles loaded on the surface.

[0040] The removal rates of Cr, Fe, Ni and Cu in electroplating wastewater are 99.2%, 99.5%, 99.1% and 98.5% respectively. Magnetic calcium sulfate whiskers loaded with composite ferrite nanoparticles on the surface are used to treat toxic gas carbonyl sulfide, with a carbonyl sulfide concentration of 500ppm, nitrogen as the balance gas, and a reaction space velocity of 15000h -1 The reaction temperature is 150°C, the water vapor content is 10%, and the loading amount in the hydrolysis tower is 3% of the tower height. Under the above conditions, after 300 minutes, the removal efficiency of carbonyl sulfide is 90%.

[0041] Example 6

[0042] 4.46g of ferrous sulfate heptahydrate was added to 100ml of electroplating wastewater (containing 1000mg / L Cr 6+ , 1000mg / L Fe 2 + 、2000mg / L Fe 3+ 、1500mg / L Ni 2+ 、800mg / L Cu 2+ and 3000mg / L Cr 3+ ), stirred for 60 minutes, added 3g of ferroferric oxide seeds with a particle size of 20nm, added CaO under stirring to adjust the pH to 12, and then aged at room temperature for 2h. Centrifuged to obtain a solid precipitate and a supernatant, the solid precipitate was dried at 80℃ for 6h and then ground to obtain magnetic calcium sulfate whiskers with composite ferrite nanoparticles loaded on the surface.

[0043] The removal rates of Cr, Fe, Ni and Cu in electroplating wastewater are 99.2%, 99.7%, 99.1% and 98.9% respectively. Magnetic calcium sulfate whiskers loaded with composite ferrite nanoparticles on the surface are used to treat toxic gas carbonyl sulfide, with a carbonyl sulfide concentration of 500ppm, nitrogen as the balance gas, and a reaction space velocity of 15000h -1 , the reaction temperature is 150°C, the water vapor content is 10%, and the filling amount in the hydrolysis tower is 3% of the tower height. Under the above conditions, after 300 minutes, the removal efficiency of carbonyl sulfide is 92%.

[0044] Comparative Example 1

[0045] The method is basically the same as Example 1, except that no CaO is added in Comparative Example 1 to adjust the pH.

[0046] 4.46g of ferrous sulfate heptahydrate was added to 100ml of electroplating wastewater (containing 1000mg / L Cr 6+ , 1000mg / L Fe 2 + 、2000mg / L Fe 3+、1500mg / L Ni 2+ 、800mg / L Cu 2+ and 3000mg / L Cr 3+ ), stirred for 60 min, then 3 g of ferroferric oxide seed crystals with a particle size of 20 nm were added, and then aged at room temperature for 2 h. The solid precipitate and the supernatant were obtained by centrifugation, and the solid precipitate was dried at 80 ° C for 6 h and then ground to obtain composite ferrite nanoparticles.

[0047] The removal rates of Cr, Fe, Ni and Cu in electroplating wastewater are 87.5%, 85.6%, 75.8% and 86.8% respectively. The composite ferrite nanoparticles are used to treat the toxic gas carbonyl sulfide, with a carbonyl sulfide concentration of 500ppm, nitrogen as the balance gas, and a reaction space velocity of 15000h -1 The reaction temperature is 150°C, the water vapor content is 10%, and the loading amount in the hydrolysis tower is 3% of the tower height. Under the above conditions, after 300 minutes, the removal efficiency of carbonyl sulfide is 80%.

[0048] Comparative Example 2

[0049] The method is substantially the same as Example 1, except that in Comparative Example 2, no ferrosoferric oxide seed crystals are added and no CaO is added to adjust the pH.

[0050] 4.46g of ferrous sulfate heptahydrate was added to 100ml of electroplating wastewater (containing 1000mg / L Cr 6+ , 1000mg / L Fe 2 + 、2000mg / L Fe 3+ 、1500mg / L Ni 2+ 、800mg / L Cu 2+ and 3000mg / L Cr 3+ ), stirred for 60 min, and then aged at room temperature for 2 h. Centrifuged to obtain a solid precipitate and a supernatant, and the solid precipitate was dried at 80°C for 6 h and then ground to obtain composite ferrite nanoparticles.

[0051] The removal rates of Cr, Fe, Ni and Cu in electroplating wastewater are 78.6%, 80.2%, 70.2% and 85.2% respectively. The composite ferrite nanoparticles are used to treat the toxic gas carbonyl sulfide, with a carbonyl sulfide concentration of 500ppm, nitrogen as the balance gas, and a reaction space velocity of 15000h -1 The reaction temperature is 150°C, the water vapor content is 10%, and the loading amount in the hydrolysis tower is 3% of the tower height. Under the above conditions, after 300 minutes, the removal efficiency of carbonyl sulfide is 75%.

[0052] The above is only a preferred implementation of the patent of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the patent of the present invention. These improvements and modifications should also be regarded as the scope of protection of the patent of the present invention.

Claims

1. A method for preparing a composite ferrite-loaded magnetic calcium sulfate whisker, characterized in that: The method is to pre-treat electroplating wastewater with ferrous sulfate, then add ferroferric oxide nanoparticles, stir and add calcium oxide, and after aging, separate solid from liquid, dry and grind to obtain magnetic calcium sulfate whiskers loaded with composite ferrite nanoparticles. Among them, electroplating wastewater contains Cr 6+ Cr 3+ In addition, it also contains Ni 2+ , Cu 2+ , Mn 2+ , Fe 2+ , Fe 3+ At least one of .

2. The method for preparing the magnetic calcium sulfate whisker of composite ferrite load according to claim 1, characterized in that, Electroplating wastewater contains Cr 6+ Cr 3+ 、Ni 2+ , Cu 2+ , Mn 2+ , Fe 2+ and Fe 3+ ; Among them, Fe 2+ , Fe 3+ 、Ni 2+ , Cu 2+ , Mn 2+ Cr 3+ Cr 6+ The concentrations are 200-2000mg / L, 500-4000mg / L, 300-3000mg / L, 10-5000mg / L, 5-1000mg / L, 100-10000mg / L, and 400-8000mg / L respectively.

3. The method for preparing the magnetic calcium sulfate whisker of composite ferrite load according to claim 1, characterized in that, The specific method of pretreatment is: adding ferrous sulfate heptahydrate into electroplating wastewater and stirring for 40-80 minutes; Among them, ferrous sulfate heptahydrate and Cr in electroplating wastewater 6+ The molar ratio is (5-30):

1.

4. The method for preparing the magnetic calcium sulfate whisker of composite ferrite load according to claim 1, characterized in that, The amount of ferroferric oxide nanoparticles added is 2-6 times the metal content in the electroplating wastewater.

5. The method for preparing magnetic calcium sulfate whiskers loaded with composite ferrite according to claim 1, characterized in that: The particle size of the ferroferric oxide nanoparticles is 20nm-1mm.

6. The method for preparing magnetic calcium sulfate whiskers loaded with composite ferrite according to claim 1, characterized in that: The pH of the solution after calcium oxide is added is 7-12.

7. The method for preparing magnetic calcium sulfate whiskers loaded with composite ferrite according to claim 1, characterized in that: Aging conditions are: room temperature, 0.5-5h.

8. The method for preparing magnetic calcium sulfate whiskers loaded with composite ferrite according to claim 1, characterized in that: The drying conditions are: 60-100℃, 3-10h.

9. Application of the composite ferrite-loaded magnetic calcium sulfate whiskers prepared by the method described in any one of claims 1 to 8 in gas purification, characterized in that: It is used to remove carbonyl sulfide contained in the gas.

Citation Information

Patent Citations

  • Purification method of wastewater containing heavy metal and arsenic

    CN102765831A

  • Solidifying comprehensive recovery method of electroplating sludge ferrite

    CN104692787A

  • Method for preparing CaF2-coated composite ferrite up-conversion fluorescence particles

    CN107828409A

  • Method for removing heavy metals in electroplating wastewater by utilizing microwaves

    CN111470684A